2017
DOI: 10.3390/ijms18112469
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab for Patients with Recurrent Multifocal Glioblastomas

Abstract: In patients with glioblastoma, antiangiogenic therapy with bevacizumab (BEV) has been shown to improve progression-free survival (PFS), but not overall survival (OS). Especially in patients with an unusual infiltrative phenotype as seen in multifocal glioblastoma, the use of BEV therapy is still more controversial. Therefore, we prepared a retrospective case series with 16 patients suffering from a multifocal glioblastoma treated with BEV. We compared these patients to a matched control cohort of 16 patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…Bevacizumab (BEV) is a monoclonal humanized antibody of the immunoglobulin G1 (IgG1) against VEGF-A was developed, inhibiting neovascularization and reducing vascular permeability then reducing focal brain edema [10]. In recurrent glioblastome multiforme, a progression free survival benefit but not overall survival benefit was reported with bevacizumab from several non-randomized trials [11,12]. As first line setting the same results were reported as improved progression free survival but not overall survival [13,14].…”
Section: Response and Toxicitysupporting
confidence: 55%
“…Bevacizumab (BEV) is a monoclonal humanized antibody of the immunoglobulin G1 (IgG1) against VEGF-A was developed, inhibiting neovascularization and reducing vascular permeability then reducing focal brain edema [10]. In recurrent glioblastome multiforme, a progression free survival benefit but not overall survival benefit was reported with bevacizumab from several non-randomized trials [11,12]. As first line setting the same results were reported as improved progression free survival but not overall survival [13,14].…”
Section: Response and Toxicitysupporting
confidence: 55%
“…While radiotherapy with concomitant and adjuvant temozolomide is the standard treatment after surgery in GBM patients, several institutions 17 have studied on prolonged administration of temozolomide and show increased survival periods of these patients or the use of Bevacizumab has similar effects in patients with mfGBM as compared to patients with GBM with single lesion. 16 The whole brain should be considered as the clinical target volume and, because of the diffuse infiltration, seems to be the most relevant area to achieve irradiation of all of the microscopic disease. 20 Radiation therapy fields, too, have the potential to be affected by a molecular signature.…”
Section: Discussionmentioning
confidence: 99%
“…Several inhibitors of PI3K/Akt/mTOR pathways have been developed for the treatment of different cancers including GBM. Clinical trials using rapamycin analogs were found to display insufficient anti-tumor activity in patients with rGBM [48,57,58,59]. A possibility could be the heterogeneity of GBM, with its redundant signaling inputs and ability to bypass blockade of individual molecules through compensatory feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…BEVA is responsible for vascular regression, tumor growth inhibition, and prolonged survival suggesting that this agent shows antitumor effects. There are evidences on direct antitumor effects of BEVA on established GBM and glioma stem-like cells [5,57,58,59,60] and BEVA shows significant anti-tumor potential as monotherapy [61]. It has also been demonstrated that BEVA monotherapy was associated with increased in intra-tumor AKT phosphorylation levels [62].…”
Section: Discussionmentioning
confidence: 99%